2008
DOI: 10.1299/jpes.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Motion and its Surrounding Liquid Motion through the Collision of a pair of Bubbles

Abstract: The interaction between bubble motion and its surrounding liquid motion through a collision of a pair of zigzagging bubbles in a rest water column was experimentally investigated. A pair of hypodermic needles and a bubble generator utilizing pressure oscillation were employed in order to exactly extract and highly reproduce the interaction between liquid-phase motion and bubble motion. The recursive cross-correlation PIV technique made it possible to obtain the accurate velocity field of surrounding liquid mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For the accurate investigation of mass transfer during bubble bouncing, an experimental setup is necessary that allows the generation of bubbles with reproducible shapes and trajectories. This can be achieved by using a hypodermic needle for bubble injection according to Sone et al [11]. With this kind of orifice the bubble interface is deformed at the exact same position each time a bubble is generated, which leads to a reproducible shape and bubble trajectory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the accurate investigation of mass transfer during bubble bouncing, an experimental setup is necessary that allows the generation of bubbles with reproducible shapes and trajectories. This can be achieved by using a hypodermic needle for bubble injection according to Sone et al [11]. With this kind of orifice the bubble interface is deformed at the exact same position each time a bubble is generated, which leads to a reproducible shape and bubble trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the interface deformations should be studied first in experiments with direct, well-defined bubble-bubble interaction. Despite the fact that bubble interactions have been already investigated by other working groups with respect to the fluid mechanical mechanisms [7][8][9][10][11] or the qualitative influence on mass transfer [12], the knowledge on the quantitative influence on mass transfer and chemical reaction is still marginal.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent 3D DNS simulations by Gumulya et al (2017) again revealed the existence of an equilibrium distance, leaving the discussion open to debate. The simultaneous release of two bubbles rising side-byside has been studied by a large number of researchers (Kok 1993;Van Wijngaarden 1993, 2005Duineveld 1995Duineveld , 1998Legendre et al 2003;Sone et al 2008;Sanada et al 2009;Hallez and Legendre 2011;Zhang et al 2019). Van Wijngaarden (1993) calculated the interaction of a pair of bubbles using a two-bubble probability density function and compared his results to the experimental data of Kok (1993).…”
Section: Introductionmentioning
confidence: 99%
“…To get the stochastic behavior of a bubble under control, there are techniques available which, e.g., use a well-defined bubble detachment that leads to a reproducible helical bubble movement [5,6], or create a vertically rising bubble by increased viscosity [7]. One disadvantage of these techniques is a short residence time of the bubble in the setup that prevents the establishment of steady conditions, necessary for many highly sensitive concentration measurement systems like Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%